"Anti‐Electrostatic" Halogen Bonding. Issue 27 (30th April 2020) - Holthoff, Jana M.; Engelage, Elric; Weiss, Robert; Huber, Stefan M.
Abstract: Halogen bonding is often described as being driven predominantly by electrostatics, and thus adducts between anionic halogen bond (XB) donors (halogen‐based Lewis acids) and anions seem counterintuitive. Such "anti‐electrostatic" XBs have been predicted theoretically but for organic XB donors, there are currently no experimental examples except for a few cases of self‐association. Reported herein is the synthesis of two negatively charged organoiodine derivatives that form anti‐electrostatic XBs with anions. Even though the electrostatic potential is universally negative across the surface of both compounds, DFT calculations indicate kinetic stabilization of their halide complexes in the gas phase and particularly in solution. Experimentally, self‐association of the anionic XB donors was observed in solid‐state structures, resulting in dimers, trimers, and infinite chains. In addition, co‐crystals with halides were obtained, representing the first cases of halogen bonding between an organic anionic XB donor and a different anion. The bond lengths of all observed interactions are 14–21 % shorter than the sum of the van der Waals radii. Abstract : Coming together : Two negatively charged organoiodine derivatives are shown to form anti‐electrostatic halogen bonds (XBs) with anions. Even though the electrostatic potential is universally negative across the surface of both compounds, DFT calculations indicate kinetic stabilization of their halide complexes. Experimentally, self‐association of the anionic XB donors is observed. Co‐crystals with halides were obtained and featured XB adducts between two or even three anions.